Protocol of a multicenter, single-blind, randomised, parallel controlled feeding trial evaluating the effect of a Chinese Healthy Heart (CHH) diet in lowering blood pressure and other cardiovascular risk factors. Issue 8 (20th August 2020) - Xie, Wuxiang; Wang, Yanfang; Sun, Jianqin; Zeng, Guo; Zhu, Huilian; Yang, Zhenquan; Gao, Pei; Yang, Jing; Feng, Lin; Lin, Pao-Hwa; Li, Ming; Xu, Jianguo; et al.
Abstract : Introduction: Unhealthy diet has been identified as the number one attributor of total mortality in China, accounting for more than 20% of total deaths. Although the Dietary Approach to Stop Hypertension (DASH) and Mediterranean diets have been proven beneficial in managing cardiovascular risk factors in Western countries, whether healthy diets with similar cardiovascular benefits can be developed that are consistent with Chinese food culture remains unknown. Methods/design: The Diet, ExerCIse and CarDiovascular hEalth (DECIDE)-Diet trial is a multicentre, single-blind, randomised controlled feeding trial to evaluate the effect of the Chinese Healthy Heart (CHH) diet, in comparison with the Chinese usual diet, in lowering cardiovascular risk factors among community residents with the increased cardiovascular risk. A total of 360 adults aged between 25 and 75 years old and with systolic blood pressure between 130 and 159 mm Hg will be recruited from four centres located in four areas representing four major Chinese cuisines: Beijing, Shanghai, Guangzhou and Chengdu. After 1 week of run-in period with local usual diet, the compliant participants will be randomised to the intervention group with the CHH diet or the control group with the usual local diet, on a 1:1 ratio, for 4 weeks. Body weight of study participants will be maintained during the entire study period. The primary outcome is the change in SBP from the baseline to the end of the study. DECIDE-Diet trial will be the first randomised controlled feeding trial to evaluate the effect of a CHH diet in lowering cardiovascular risk factors. This trial will provide compelling evidence on the CHH diet in effect of improving cardiovascular health among Chinese food consumers all around the world. Ethics and dissemination: This trial adheres to the Declaration of Helsinki and guidelines of Good Clinical Practice. Signed informed consent will be obtained from all participants. The trial has been approved by the Peking University Institutional Review Board (approval number: IRB00001052-18094). The results will be disseminated through academic conferences and publications in international peer-reviewed journals. Trail registration number: ClinicalTrials.gov Registry (NCT03882645 ); Pre-results.